1988
DOI: 10.1288/00005537-198811000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Reflux as an etiological factor of carcinoma of the laryngopharynx

Abstract: This study examined charts and 16-mm pictures or videotapes of 138 patients with carcinoma of the larynx treated during the last 10 years. Among these patients, 19 were nonsmokers and nondrinkers or only light social drinkers with moderate to severe gastroesophageal reflux (GER). Serial cinephotographs are presented with follow-up of up to 10 years. The common presence of GER in these nonsmoking, nondrinking patients and the probable role of this chronic irritative disorder as a causative agent in carcinoma of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
5

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 11 publications
2
95
0
5
Order By: Relevance
“…-Gastropharyngeal reflux: Gastroesophageal reflux has been related to increased risk of laryngeal SCC, especially among patients who lack other major risk factors (83). Gastroesophageal reflux may act as a promoter in the presence of tobacco and alcohol (84).…”
Section: -Diet and Nutritional Factorsmentioning
confidence: 99%
“…-Gastropharyngeal reflux: Gastroesophageal reflux has been related to increased risk of laryngeal SCC, especially among patients who lack other major risk factors (83). Gastroesophageal reflux may act as a promoter in the presence of tobacco and alcohol (84).…”
Section: -Diet and Nutritional Factorsmentioning
confidence: 99%
“…In 1976, it was first suggested that inflammatory disease could cause laryngeal cancer (23), and in the late 1980s, it was further proposed that gastroesophageal reflux could play a causal role in laryngeal and pharyngeal carcinogenesis (14,17). Until recently, the only available data on this subject were from uncontrolled case series, of which some authors interpreted their data in favor of an association (13)(14)(15)(16)(17), others against (24). In 2001, the first controlled study addressing this issue was published in the form of a nested case-control study in the United States, demonstrating a moderately strong association between reflux-related inpatient discharge diagnoses and cancers both of the larynx and pharynx (18).…”
Section: Discussionmentioning
confidence: 99%
“…A link between gastroesophageal reflux and laryngeal and pharyngeal cancers has also been suggested, based on results from several case series (13)(14)(15)(16)(17). Recently, a 2-fold increased risk for each of these two tumors was found among persons with a history of gastroesophageal reflux disease in a nested case-control study conducted using the computerized database of veterans' hospitals across the United States (18).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, LPR has also been implicated in the development of laryngeal carcinoma and stenosis, recurrent laryngospasm, and cricoarytenoid joint fixation, as well as with many other otolaryngology-related conditions, including globus pharyngeus, cervical dysphagia, and subglottic stenosis. [4][5][6][7][8][9]. Patients with "reflux laryngitis" (LPR) present with hoarseness, but almost two thirds deny ever having heartburn.…”
Section: Introductionmentioning
confidence: 99%